Administration of Spinach and Tomato Juice to Overcome Nutrition Deficit in third Trimester Pregnant Women with Anemia: Case Study: Pemberian Jus Bayam Dan Tomat Untuk Mengatasi Defisit Nutrisi Pada Ibu Hamil Trimester Tiga Dengan Anemia: Studi Kasus - Annisa Imania; Hayuni Rahmah (Politeknik Kesehatan Kemenkes RI Jakarta I, 2021)
Pregnant is the part of reproduction process as Human. Nursing Care Plan by Giving Spinach and Tomato Juice toDecrease Nutrition Deficit for 3rd Trimester Pregnant Woman with Anemia. Pregnancy is one part of the process ofhuman reproduction. Nutrition is one of the factors that influence pregnancy. Nutritional needs during pregnancyincrease, one of them is iron which plays a role in the formation of red blood cells. Physiologically, in pregnant womenan increase in blood volume in large numbers. If not balanced with the consumption of sufficient substances can causeanemia. The purpose of this paper is to provide an analysis of the implementation of nursing care nutritional deficitproblems for pregnant women with anemia. Anemia is a state of blood hemoglobin (Hb) levels lower than normal levelsaccording to age and sex. This articles using case study methods, and using instrument measuremement Hb levels beforeand after the intervention. One nursing intervention to overcome anemia is by giving spinach juice and tomatoes thatcontain iron. Spinach juice and tomatoes are gave to pregnant woman for 10 days. The results obtained indicate that theclient experienced an increase in hemoglobin level of 10.1 g / dl from 8,7 gr/dL. This study prove by giving spinach andtomato juice for 10 days increasing Hb levels in third trimester pregnant woman.